Power struggle on subjectivity and foreign policy: a post-structuralist analysis of JDP’s policies towards the United States (2002–2016) - BEYRİBEY, TUNCER (My University, 2023)
This article analyses Turkish foreign policy towards the United States (US) during the Justice and Development Party (JDP) era by using a post-structuralist approach. Post-structuralism posits that foreign policy is a political practice reflecting domestic power struggles. Moreover, subjectivities and foreign policy practices are neither universal, objective, nor predetermined, since they are co-constitutive. From this theoretical perspective, the article explores the JDP’s \"foreign policy\" discourse on US-Turkish relations, highlighting discursive practices in legitimising specific subjectivities, such as \"conservative\" and \"Muslim\" ones, as \"inherent\" origins of foreign policy conduct. In two phases, 2002–2009 and 2009–2016, it analyses how changes in JDP’s foreign policy preferences towards the US function to legitimise or marginalise particular subjectivities in its power struggle vis-à-vis \"Kemalist\" state elites. Ultimately, the article concludes that the JDP’s discourse exhibits a continuity in hegemonising the \"Islamic\" subjectivity ascribed to the Turkish population, despite changes in foreign policy decisions.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Genel Sosyoloji ve Metedoloji; Bilim, Teknoloji ve Toplum; Social Sciences and Humanities; Sociology; General Sociology and Methodology; Science, Technology and Society; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; SOSYOLOJİ; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; SOCIOLOGY; POLITICAL SCIENCE; Sosyoloji ve Siyaset Bilimi; Sosyal Bilimler ve Beşeri Bilimler; Siyasi bilimler ve Uluslararası İlişkiler; Sociology and Political Science; Social Sciences & Humanities; Political Science and International Relations; JDP; post-structuralism; Turkey-US relations; Turkish foreign policy